2016
DOI: 10.3390/toxins8030060
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Bioinsecticidal Activity of Solanaceae Alkaloids

Abstract: Only a small percentage of insect species are pests. However, pest species cause significant losses in agricultural and forest crops, and many are vectors of diseases. Currently, many scientists are focused on developing new tools to control insect populations, including secondary plant metabolites, e.g., alkaloids, glycoalkaloids, terpenoids, organic acids and alcohols, which show promise for use in plant protection. These compounds can affect insects at all levels of biological organization, but their action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
158
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(169 citation statements)
references
References 142 publications
1
158
0
10
Order By: Relevance
“…Our findings raise the possibility that similar highly virulent strains may be found in the rhizosphere of plants having insecticidal properties. The Metarhizium isolates from rhizospheric soils of papaya, chilli, and neem, the plants having insecticidal properties , from widely separated families, seem to corroborate this view. A concerted search for endophytic entomopathogens, including Beauveria , Nomuraea , and Lecanicillium , in plants not attacked by chewing insects, may yield highly virulent strains against H. armigera and other insects, making entomopathogenic fungi more cost‐effective for agriculture.…”
Section: Discussionmentioning
confidence: 74%
“…Our findings raise the possibility that similar highly virulent strains may be found in the rhizosphere of plants having insecticidal properties. The Metarhizium isolates from rhizospheric soils of papaya, chilli, and neem, the plants having insecticidal properties , from widely separated families, seem to corroborate this view. A concerted search for endophytic entomopathogens, including Beauveria , Nomuraea , and Lecanicillium , in plants not attacked by chewing insects, may yield highly virulent strains against H. armigera and other insects, making entomopathogenic fungi more cost‐effective for agriculture.…”
Section: Discussionmentioning
confidence: 74%
“…Solanaceous species are often rich in alkaloids. The toxicity of these alkaloids to humans and other animals can range from mild irritation to lethality even in small quantities (Chowański et al 2016). The poisonous species in this family include Atropa belladonna L., Hyoscyamus niger L. and Datura stramonium L. The family includes an important economic plant, tobacco (Nicotiana tabacum L.), which contains highly toxic alkaloids such as anabasine, anatabine, nicotine and nornicotine (Sun et al 2013).…”
Section: Corresponding Authormentioning
confidence: 99%
“…Thus, some flavonoids extracted from the Japanese larch and Larix leptolepis (Lamb) showed strong feeding deterrent activities against Coptotermes formosanus (Shiraki) (Ohmura et al, 2000;Chen et al, 2004). Recently Chowański et al (2016) reported the toxicity caused by alkaloids from few Solanaceae plants. According to these authors, both formulations (metabolites and water/alcohol extracts) showed lethal and sublethal effects on tested termites and other pestiferous insects.…”
Section: Introductionmentioning
confidence: 99%